EDITORIAL - Kadankavil, Thomas (Journal of Dharma, 1988)
Spirituality is basic to every religion. Religious discourses and literature about spirituality invariably take up the issue of the contrast between the way of life and death, between the way of the spirit and that of the world, between the narrow and the broad way, between light and darkness, The great divide between the humanists and the theists is based on how each of them belongs to the one or the other of this contrasting reality. For each camp the other is holding, in Sartrean terms "a bad faith," a faith characterized by intellectual dishonesty, the rejection of thoughts from consciousness, and the refusal to face disagreeable facts. For each the other is "the bad conscience of their age," which calls for a self examination from both sides. "In bad faith, it is from myself that I am hiding the truth." J Neither the religious, nor the secular would consciously choose to stay in ’bad faith: whatever it may cost them. The antagonism between them now has reached a feverish pitch that the one heaps ridicule on the other. Nietzsche holds up to ridicule the accepted ideals of the Judea-Christian religion and Greek rationalism, describing them as reversals of the true values.